An international review of the characteristics of viral nucleic acid-amplification testing (NAT) reveals a trend towards the use of smaller pool sizes and individual donation NAT - Faddy, Helen M. (2024)
Background and Objectives: Nucleic acid-amplification testing (NAT) is used forscreening blood donations/donors for blood-borne viruses. We reviewed global viralNAT characteristics and NAT-yield confirmatory testing used by blood operators.Materials and Methods: NAT characteristics and NAT-yield confirmatory testingused during 2019 was surveyed internationally by the International Society of Blood Transfusion Working Party Transfusion-Transmitted Infectious Diseases. Reportedcharacteristics are presented herein.Results: NAT was mainly performed under government mandate. Human immunodeficiency virus (HIV), hepatitis C virus (HCV) and hepatitis B virus (HBV) NAT was performed on all donors and donation types, while selective testing was reported forWest Nile virus, hepatitis E virus (HEV), and Zika virus. Individual donation NAT wasused for HIV, HCV and HBV by 50% of responders, while HEV was screened inmini-pools by 83% of responders performing HEV NAT. Confirmatory testing forNAT-yield samples was generally performed by NAT on a sample from the samedonation or by NAT and serology on samples from the same donation and a followup sample.Conclusion: In the last decade, there has been a trend towards use of smaller poolsizes or individual donation NAT. We captured characteristics of NAT internationallyin 2019 and provide insights into confirmatory testing approaches used for NATyields, potentially benefitting blood operators seeking to implement NAT.